Information Literacy and the Digital divide: challenging e-Exclusion in the Global South - Dunn, Hopeton [S.] (New York: Information Science Reference, 2010, 2016)
With the increasing spread of information and communications technologies (ICTs) globally, there is heightened debate about the continuing disparities of access and usage. The dialogue has proceeded in many respects oblivious of the centrality of information literacies in capacity building measures to redress the digital divide. This chapter examines both the concepts of the digital divide and information literacies and regards them as highly compatible in their application to the global south following a detailed analysis of issues such as orality and literacy, globalization from below and effective access to technology networks. The chapter concludes with a range of recommendations relating to reforms in strategic thinking and policy planning. The call for heightened emphasis on education including information literacies forms the centerpiece of an analysis grounded in both theory and empirical research.
Chapter 18.
Keywords: Digital divide - - Prevention - - Research; Internet - - Social aspects